Living from milk: Transforming dairying in Tanzania - International Livestock Research Institute (International Livestock Research Institute, 2014)
This is the story of Faustina Akyoo, a dairy farmer from Tanga in Tanzania, who talks about the benefits of dairying and being a member of the Tanga Dairy Platform